ARCHITECTURAL VALUES AND PERCEPTION BETWEEN RHETORIC AND REALITY - PAROQUE BOLLIN, PASORY MORDERNAS (International Journal of Multidisciplinary Research and Studies, 2021)
Throughout history, style values have invariably underlined a given style of architecture. Themanner architects and subject area critics distinguish between them vary from that of thepublic. A style well perceived by civil society was read as pathological by architecturalacademia. This paper examines the values and perceptions of up to date design byarchitects and civil society. Through qualitative methodology, a project by each of the followingleading contemporary architects – Renzo Piano, Norman Foster and Rem Koolhaas – wereanalyzed. The selected designs, all commissioned not more than a decade ago, vary in locationsfrom Malta to Lebanon to India. The study concludes that design values and perceptions ofarchitecture as a scan by members of the subject area profession don’t tally with those of thepublic. The emphasis by architects is on the aesthetic while the non-architects focus on theutilitarian dimension. Furthermore, the rhetorical language which architects use is not read assuch by the public. The assessment of the public is based on the existential reality which theyexperience. The perception of civil society matters; it’s at the core of subject area stylevalues.